Controlled grafting of dialkylphosphonate-based ionic liquids on γ-alumina: design of hybrid materials with high potential for CO2 separation applications. Issue 35 (25th June 2019) - Pizzoccaro-Zilamy, M. A.; Piña, S. Muñoz; Rebiere, B.; Daniel, C.; Farrusseng, D.; Drobek, M.; Silly, G.; Julbe, A.; Guerrero, G.
Abstract : Grafting of diethylphophonate-based ILs onto γ-Al2 O3 powder in solvothermal condition was achieved on mesoporous γ-alumina powder and membrane (A = organic spacer). Abstract : In this work we provide a detailed study on grafting reactions of various dialkylphosphonate-based ILs. Special attention has been devoted to a comprehensive investigation on how the nature of the anion and the organic spacer composition (hydrophilic or hydrophobic groups) could impact the grafting densities and bonding modes of phosphonate-based ILs anchored to γ-alumina (γ-Al2 O3 ) powders. For the first time, the bonding of phosphonate-based ILs with only surface hexacoordinated aluminum nuclei was established using both solid-state 31 P– 27 Al D-HMQC and 31 P NMR experiments. It has been demonstrated that the grafting of dialkylphosphonate-based ILs is competing with a hydrolysis and/or precipitation process which could be attractively hindered by changing the anion nature: bis(trifluoromethane)sulfonylimide anion instead of bromide. In additon, independently of the chosen spacer, similar reaction conditions led to equivalent grafting densities with different bonding mode configurations. The CO2 physisorption analysis on both pure ILs and grafted ILs on alumina powders confirmed that the initial sorption properties of ILs do not change upon grafting, thus confirming the attractive potential of as-grafted ILs for the preparation of hybrid materials in a form of selective adsorbers or membranes for CO2 separation applications.